2001
DOI: 10.1103/physrevlett.87.273401
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Rydberg Series inC60

Abstract: Rydberg series of C60 are reported for the first time. The Rydberg states are seen in photoelectron spectra using ultrashort pulsed-laser excitation, where the excited states formed are ionized with one further photon from the same laser pulse. The structure is observed for pulse durations as short as 100 fs with indications of residual structure for even shorter pulse excitation. The production mechanism is discussed and the Rydberg states are modeled by analytically solving the Schrödinger equation with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 19 publications
5
44
0
Order By: Relevance
“…Angularly resolved photoionization by ultrashort laser pulses has been advocated for probing the electronic dynamics before the onset of significant nuclear motion (see, e.g., [27][28][29][30][31] [36,37], and efficient high-harmonic generation [38][39][40]. The ionization and fragmentation of C 60 have been investigated extensively in the past (see, e.g., [35,[41][42][43][44][45][46][47]). C 60 is very stable and is one of the few molecular systems for which the ionization energy is smaller than the lowest fragmentation threshold.…”
mentioning
confidence: 99%
“…Angularly resolved photoionization by ultrashort laser pulses has been advocated for probing the electronic dynamics before the onset of significant nuclear motion (see, e.g., [27][28][29][30][31] [36,37], and efficient high-harmonic generation [38][39][40]. The ionization and fragmentation of C 60 have been investigated extensively in the past (see, e.g., [35,[41][42][43][44][45][46][47]). C 60 is very stable and is one of the few molecular systems for which the ionization energy is smaller than the lowest fragmentation threshold.…”
mentioning
confidence: 99%
“…The same group also showed the formation of nearly free electron bands when fullerenes aggregated to form a two-dimensional crystal on the metal surface, indicating that these could be interesting systems for molecular electronics applications if the excitation energy of the SAMOs could be tuned to be closer to the Fermi energy. The excited SAMOs were observed earlier in gas-phase C 60 by femtosecond photoelectron spectroscopy; however, they were not specifically identified as such [5], and they have also been observed in two-photon photoemission experiments on C 60 layers deposited on surfaces [6].…”
Section: S-samo P-samo D-samomentioning
confidence: 95%
“…The details of the experimental techniques have been provided in previous publications [5,8,9] and will be only briefly described here. The original studies that reported the excitation and subsequent single-photon ionization of Rydberg states in C 60 were carried out with a combined linear time-of-flight photoelectron spectrometer and a time-of-flight mass spectrometer (MS) [5,10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations